Auctions with Downstream Interaction - Philippe Jehiel; Benny Moldovanu (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
We study auctions for an indivisble object. The outcome of the auction influences the future interaction among agents. The impact of that interaction on agent i is assumed to be a funciton of the agents' valuations. While agent's i valuation is private information to i, other valuations are not observable by i at the time of the auction. We derive equilibrium bidding strategies for second price auctions in which the seller may impose reserve prices or entry fees, and we point out differences between the cases where impacts (which we call externalities) are positive or negative. Finally, we study the effect of reserve prices and entry fees on the seller's revenue.
Keywords: 330